Intestinal parasitic infections among BaAka Pygmies and Bantu people living in the rain forests in Lobaye Prefecture, Central African Republic - Monika Pintal-Ślimak; Wanesa Wilczyńska; Konrad Grzeszczak; Marta Grubman-Nowak; Krzysztof Korzeniewski (International Maritime Health)
BACKGROUND: Central African Republic (CAR) is one of the poorest countries in the world with nearly 65% of its inhabitants living in extreme poverty, and 87% lacking access to safely managed sanitation facilities. Poor sanitation and limited access to healthcare contribute to high transmission of intestinal parasitoses. The present study aimed to assess the occurrence of intestinal parasitic infections (IPIs) in two separate ethnic groups inhabiting the rainforests in the Lobaye Prefecture in the southern parts of the CAR: the nomadic BaAka Pygmies and the sedentary Bantu people. In addition, the results obtained from the examination of the Pygmy people were compared to the results of the 2021 study on the occurrence of IPIs in a Pygmy community inhabiting the Sangha-Mbaéré Prefecture in the CAR, in the context of the effectiveness of mass deworming actions among the population living in the forest ecosystem. MATERIALS AND METHODS: Stool samples for parasitological examination were collected from 170 patients (145 Bantu people and 25 BaAka Pygmies) in September 2024 at a healthcare facility in Bagandou, the Lobaye Prefecture, CAR. The exclusion criterion was taking antiparasitic drugs within four weeks before collecting the biological material for testing. The collected biological material was fixed in SAF fixative, and next it was transported to the Department of Epidemiology and Tropical Medicine at the Military Institute of Medicine – the National Research Institute in Poland, where it was examined by light microscopy; the specimens were prepared for examination using three different methods (a direct smear in Lugol’s solution, decantation with distilled water, the Fülleborn’s flotation method). RESULTS: A total of 38.2% of the study participants were found to be infected with at least one clinically significant parasitic species. Apart from potentially pathogenic Blastocystis spp. and non-pathogenic protozoa, hookworm, Giardia intestinalis and Ascaris lumbricoides were found to be the most prevalent parasitic species in the study participants. More than 60% of the participants were found to be co-infected with at least two different parasitic species. The occurrence of IPIs was significantly higher in BaAka Pygmies compared to the sedentary Bantu people. It also demonstrated that the infection rate was lower in older age groups. CONCLUSIONS: The study demonstrated a high occurrence of intestinal parasitic infections both among BaAka Pygmies and in the Bantu people inhabiting the Lobaye Prefecture. Mass deworming campaigns conducted by catholic missionaries, as well as non-governmental organisations, are not effective in reducing the number of STH cases in the local communities. Continuous exposure to risk factors and the unique lifestyle of the local residents put them at risk of permanent reinfections.